APLIKASI PERKONGRUENAN DALAM MENYELESAIKAN SISTEM PERSAMAAN LINEAR DUA PEUBAH - Yuni Yulida; Muhammad Ahsar Karim (Mathematics Study Program, Faculty of Mathematics and Natural Sciences, Lambung Mangkurat, 2009)
This paper discusses the determination of existention and solution of linearequation system with two variables written as:a x b y ca x b y ca x b y c    2 2 21 1 where x, y are integers, and n n n a ,a ,,a ,b ,b ,,b ,c ,c ,,c 1 2 1 2 1 2 are non-negativeintegers, using the application of linear congruency